Experimental infection by Aeromonas hydrophila in Piaractus mesopotamicus: DL50, neurological disturbances, and mortality - Claudiano, Gustavo S. [UNESP]; de Moraes, Flávio Ruas [UNESP]; Fernandes, Dayanne C. [UNESP]; Vantini, Juliana S. [UNESP]; Yunis-Aguinaga, Jefferson [UNESP]; Eto, Silas F. [UNESP]; Marinho-Neto, Fausto A. [UNESP]; Macedo, Hugo J. A.; Manrique, Wilson G.; Moraes, Julieta R. E. [UNESP] (Springer Nature, 2020)
Aeromonosis is an infectious disease of high occurrence in captive fish. It manifests mainly as hemorrhagic septicemia. This study aimed to evaluate the physiopathology manifestations of septic aeromonosis in Piaractus mesopotamicus, considering its clinical manifestations, mortality rates, anatomopathology, and anti-iNOS immunolabeling in the brain. Fish were inoculated in the coelomic cavity with increasing concentrations of A. hydrophila: 1.5 × 108; 1.8 × 108; 2.1 × 108; 2.4 × 108; 2.7 × 108 CF mL−1, histopathology, and anti-iNOS immunolabeling in brain. The animals present erratic swimming (swirling), depigmentation, petechiae, skin suffusions, and high mortality rates up to 100% according to the inoculum concentration. The DL50-96 h was estimated in 1.806 × 108 CFU mL−1. Fish inoculated with 2.1 × 108 CFU mL−1 presented 100% mortality rate. Fish presented neurological signs, congestion, extensive hemorrhage, and glial cells activity confirmed by the anti-iNOS labelling. In addition, the inoculated bacteria was reisolated from the brains. The results demonstrated that aeromonosis physiopathology is multifactorial and the observed neurological signs were caused by the inoculated bacteria. These findings highlight the need for differential diagnosis with other infections that produce encephalitis.
Keywords: Aeromonosis; Brain infection; Hemorrhagic septicemia; Inflammation